The Play of the Weather, Merry Report, and Henrician Court Culture - Betteridge, Thomas (Early Theatre, 2026)
This essay examines John Heywood’s Henrician court drama The Play of the Weather to argue that in this play Heywood articulates a specifically courtly dramaturgy and politics focused on the vice figure, Merry Report. The first part of the essay discusses the nature of Henry’s court, while the second part discusses in detail Merry Report’s performance as a court officer. Overall, my focus in this this essay is on Heywood’s construction in Play of the Weather of the court as a privileged theatrical space for the debate and reconciliation of even such contentious matters as the English weather.